Different sources of nitrogen in potato cultivation and the management of common scab - da Silva Mira, Thiago Jose (Revista Agrogeoambiental, 2023)
Potato (Solanum tuberosum L.) is native to South America and is the main vegetable grown in Brazil and worldwide. One of the diseases that can attack potato crops is the common scab, caused by the bacteria Streptomyces scabies, which affect roots and tubers. The objective of this research was to evaluate the effect of different sources of cultivation on potato crop in the management of common potato scab. The experimental design was in randomized blocks (DBC) containing five treatments urea (45% N), ammonium sulfate (20% N), protected urea (45% N), organomineral (0.75% N) and control (0% N). N) and four replications, in a total of 20 pots. The bacterium was removed from infected potato tubers and isolated in petri dishes containing YMA (Yeast, Manitol, Agar) culture medium. The bacterium was inoculated into the soil 15 times, seven days before planting. Seeds were distributed in pots with a capacity of 8 L, in a proportion of 2:1 (earth and sand), which were placed in a greenhouse. Fertilizing for planting and coverage was carried out according to the requirements of the crops: fertilization with urea and ammonium sulfate was carried out once at planting and twice at the top dressing; fertilizing with protected urea and organomineral was carried out once at planting and once at the top dressing; and nitrogen fertilization was not performed in the control treatment. The tubers were harvested 90 days after sowing. The variables analyzed were severity (graded) and incidence, counting the number of contaminated tubers, tuber weight yield of each plot, number of leaves, number of stems, and plant height. It was observed that the treatments with urea and ammonium sulfate had a lower percentage of common scab incidence, with an average incidence of 6.74% and 8.42%, respectively, followed by protected urea (8.90%). Urea and ammonium sulfate were efficient in reducing potato scab and increasing tuber production.